Bearing Velocity Determination with Lifting Wheel Set Detectionfor HXD3C Locomotive - ZENG You-heng; CHEN Xi; LIU Shi-yong (机车电传动)
Aim to the quality problems of HXD3C locomotive, characteristic of HXD3C locomotive wheel set driving control wasdiscussed, and the key factor that lifting wheel set detection could not determine bearing velocity was pointed out. Technical routine of bearingvelocity determination with lifting wheel set detection was selected, and design idea and scheme to determine bearing velocity with hardwarewere presented and a novel signal generation device was developed. The novel devices had excellent applying effect, which not only providedstable data for acquisition, but also removed safety incipient fault for garage lifting wheel set operation, what is more, it presented a newvelocity determination idea for other locomotive.